2012
DOI: 10.1111/imr.12022
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of enhanced HIV spread through T‐cell virological synapses

Abstract: An elaborate network of cell-cell interactions in the immune system is essential for vertebrates to mount adaptive immune responses against invading pathogens. For lymphotropic viruses such as the human immunodeficiency virus type 1 (HIV-1), these immune cell interactions can also promote the spread of the virus within the host. The main target of HIV-1 infection is the CD4(+) helper T lymphocyte, a cell type that is responsible for coordinating immune responses and modulating effector responses to foreign an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
45
0
2

Year Published

2014
2014
2018
2018

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(52 citation statements)
references
References 106 publications
(165 reference statements)
5
45
0
2
Order By: Relevance
“…Previous studies showed that CD4-independent infection of epithelial or neural cells by certain strains of HIV-1 can occur, suggesting that HIV-1 can employ alternate receptors for mucosal entry (7)(8)(9)(10). The interaction of HIV-1 with such alternate receptors can be adhesive in nature, like those described for cell-cell transmission (11,12), and therefore could potentially facilitate the mucosal entry of HIV-1. Thus, any mode of disruption of viral adhesion to epithelial cells could be a strategy to hinder mucosal entry of HIV-1.…”
mentioning
confidence: 99%
“…Previous studies showed that CD4-independent infection of epithelial or neural cells by certain strains of HIV-1 can occur, suggesting that HIV-1 can employ alternate receptors for mucosal entry (7)(8)(9)(10). The interaction of HIV-1 with such alternate receptors can be adhesive in nature, like those described for cell-cell transmission (11,12), and therefore could potentially facilitate the mucosal entry of HIV-1. Thus, any mode of disruption of viral adhesion to epithelial cells could be a strategy to hinder mucosal entry of HIV-1.…”
mentioning
confidence: 99%
“…The phenomenon of anti-integrin induced cell aggregation has been used as a common approach to investigate integrin function as reported by several studies (Andrew D P, et al, 1994;Ruegg C, et al, 1992;Zeller Y, et al, 2001). The formation of cell aggregates increases cell-cell contact, which in turn enhances viral infection (Alvarez R A, et al, 2011;Dale B M, et al, 2013;Liao Z, et al, 2000). This represents an important confounder and suggests that antibody engagement of α 4 β 7 is not an appropriate approach to determine the significance of α 4 β 7 in HIV-1 infection of primary lymphocytes (Parrish N F, et al, 2012).…”
Section: Blockade or Knockdown Of α 4 β 7 Expression On Cd4 + T Cellsmentioning
confidence: 99%
“…In cell-free infection, infectious viral particles present in the extracellular milieu infect CD4 þ T cells via diffusion-limited spread. In cell-to-cell infection, on the other hand, HIV-1 is conveyed more directly from infected to uninfected cells, where virions are captured in narrow intercellular clefts and the physical connection formed between donor and target cells, known as the virological synapse, actively contributes to the efficient viral expansion (Dale et al, 2013;Sattentau, 2008;Zhong et al, 2013b). Moreover, events in the process of cell-to-cell HIV infection are chronologically specified, i.e., HIV viral transfer, an early event observed immediately after formation of cell-to-cell contact, is followed by a later, sometimes independent, event, HIV productive transmission, which ensures the infection .…”
Section: Introductionmentioning
confidence: 99%